Factors Associated with the Risk of Nutritional Problems in Children With Cancer - Puspa Sari; Hellena Deli; Gans Indriati (CV. Rayyan Dwi Bharata, 2024)
Childhood cancer, the effects of treatment result in a weakening of the immune system, making sufferers susceptible to infection and creating a risk of nutritional problems. The aim is to find out risk factors for nutritional problems in children with cancer at Arifin Achmad Hospital, Riau Province. This research is quantitative with a correlational descriptive approach and cross-sectional survey design. This population is children with cancer totaling 41 respondents using purposive sampling techniques. The questionnaire used by NRS-PC. Data analysis is bivariate analysis with chi-square. The research results showed that 36 respondents (87.8%) were at risk of nutritional problems. The results of the research correlation showed that there was no significant relationship between age, gender, diagnosis, time of diagnosis, and BMI on the risk of nutritional problems. The results of the study also showed that there was a significant relationship between chemotherapy phase factors and the risk of nutritional problems. The conclusion of the research is that there is a risk of nutritional problems in children with cancer, the cause of which is the cancer they are suffering from, namely chemotherapy phase factors related to the patient and the treatment they are undergoing.